Vitamin D Status and Its Influence on the Health of Preschool Children in Hangzhou - Chen, Zhaojun; Lv, Xi; Hu, Wensheng; Qian, Xia; Wu, Ting; Zhu, Yunxia (Frontiers in Public Health, 2021)
Objective: Vitamin D deficiency and insufficiency in children are global public health problems. However, few studies have focused on vitamin D status in healthy preschool children, especially in Asia. This study aimed to investigate vitamin D status and host-related factors in healthy preschool children in Hangzhou to analyze the impact of low vitamin D levels (<30 ng/mL) on health outcomes (obesity, early childhood caries and respiratory tract infections). Methods: A total of 1510 healthy children aged 24-72 months from 15 kindergartens in Hangzhou were included. Data on the children’s gender, age, BMI, caries, and blood samples available for vitamin D analysis were collected from June to August 2018. A total of 325 children aged 36-48 months took part in a survey on the frequency of respiratory tract infections in the last year. Results: The children’s mean 25(OH)D level was 28.01±7.29 ng/mL. A total of 11.4% of the children had vitamin D deficiency, and 52.6% had vitamin D insufficiency. Only 36.0% had vitamin D sufficiency. No significant difference was found by gender or BMI group. However, children in the obesity group had the highest prevalence of vitamin D deficiency and the lowest 25(OH)D levels. A significant negative correlation was found between the 25(OH)D level and child age (r=-0.144, p<0.001). Regression analysis showed that the children’s 25(OH)D levels decreased by 0.17 ng/mL/month with age. In addition, children with low vitamin D levels might increase the risk of obesity and early childhood caries. Multiple linear regression indicated that the number of caries in children increased by 0.08 per 1 ng/mL decrease in the 25(OH)D level (β =-0.08, p<0.001). Conclusion: Vitamin D deficiency/insufficiency is a serious problem among healthy preschool children in Hangzhou. Public health policies or interventions should be implemented to ensure that preschool children have adequate vitamin D to reduce the risk of related diseases.